Chromato-mass spectroscopy of tinctures from the underground part of Valerian plants growing in Zaporizhzhia region - V. M. Odyntsova; Yu. I. Korniievskyi; D. Yu. Skoryna; V. Н. Korniievska (Zaporozhye State Medical University, 2022)
Modern sedatives used in medical practice can be of both synthetic and natural origin. It is known that the best phytosedative is valerian. In the 18th century, valerian was included in all European pharmacopeias. High efficiency, good tolerability, and virtually no side effects ensure the widespread use of valerian and its phytopreparations in medical practice, especially for the treatment of geriatric patients. Despite this, valerian remains understudied due to its extreme polymorphism. The aim of the work is to determine the component composition of valerian tinctures made from rhizomes with valerian roots of different species growing in the Zaporizhzhia region by gas chromatography and to carry out their comparative analysis. Materials and methods. Samples of rhizomes with valerian roots made from medicinal plant raw materials of valerian according to the traditional production recipe (Tinctura Rhizomata cum radicibus Valerianae (1:5)) from different species of valerian growing in the Zaporizhzhia region were selected for experimental studies: Valerian stolonifera Czern. - Kantserivska Balka, Zaporizhzhia district, Zaporizhzhia region; V. exaltata Mikan. - Shyroke village, Vasylivskyi district, Zaporizhzhia region; V. tuberosa L. - Khortytsia Island, Zaporizhzhia; V. collina Wallr. - right bank of the Dnieper River, Zaporizhzhia. The component composition of valerian tinctures was studied using an Agilent 7890B gas chromatograph with a mass spectrometric detector 5977B. Results. The component composition of tinctures from the underground part of valerian plants growing in the Zaporizhzhia region was identified and analyzed with chromato-mass spectrometry. Conclusions. 55 components in valerian tincture from underground raw materials of Valeriana stolonifera Czern. were identified with gas chromatography: V. exaltata Mikan. - 48, V. tuberosa L. - 54, V. collina Wallr. - 51. Analyzing the obtained data, we can conclude that valerian tinctures differ in both quantitative and qualitative composition. Only compounds 7 and 9 coincide in tinctures from underground parts of all four types of valerian. Since the tinctures were made following the standard technology, the content of components in medicinal plant raw materials depends on the type, place of growth, environmental conditions, time of collection, drying of raw materials. The results of the study confirm the prospects of using the underground part of the studied plants of the genus Valerian to create new drugs and phytopreparations on their basis. However, given the extreme polymorphism of valerian for the introduction into the culture of promising species that grow in Ukraine, it is necessary to conduct more in-depth pharmacognostic and pharmacological studies of plants of this genus.